Estimation of Selenium Level in Serum of Iraqi Thalassemic Patients After Ferritin Assay - Sundus Kh. Al-Khazraji (College of Pharmacy / Mustansiriyah University, 2010)
Background: Selenium, a trace element with antioxidant properties, decreased in patients with blood disorders. Objective: To see if blood transfusion in those patients with thalassemia corrects the level of selenium in their blood. Materials & Methods: Seventeen patients enrolled in this small study, ten of them females and seven were males, their ages were ranged from 1.5-73 years. Ferritin and selenium levels were estimated using Mini-Vidas and atomic absorption technique respectively. Results: Decreased selenium level in both non-bloods transfused (0.33±0.17ppm) and blood transfused patients (0.30±0.24ppm) show no effect of blood transfusion on the level of this trace element. Conclusion: Selenium supplement is the only way to elevate the level of this element in the body with some precautions of selenium toxicity. Further studies on this subject are recommended.